2004
DOI: 10.2320/matertrans.45.703
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ultrasonic Soldering Technique for Lead-Free Solders

Abstract: Sn-Bi alloy is one of the representative low temperature type lead-free solders. However, the bonding properties of the Sn-Bi solder are not good. The reason for such properties is related to Bi microcrystallines that segregate at the interface between the solder and a Cu substrate. We found that ultrasound improves the bonding strength for the Sn-Bi alloy system solders by dispersing and miniaturizing the Bi crystals. To achieve such dispersion, we invented a novel ultrasonic soldering technique. By using thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This process propagates ultrasonic vibrations through substrates directly without using a solder bath (Faridi et al, 2000). Kago et al (2004) conducted this type of ultrasonic soldering for joining Cu substrates. Naka and Hafez (2003) reported that joints of Al 2 O 3 to Cu using Zn-Al filler alloy were successfully obtained.…”
Section: Introductionmentioning
confidence: 99%
“…This process propagates ultrasonic vibrations through substrates directly without using a solder bath (Faridi et al, 2000). Kago et al (2004) conducted this type of ultrasonic soldering for joining Cu substrates. Naka and Hafez (2003) reported that joints of Al 2 O 3 to Cu using Zn-Al filler alloy were successfully obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al (2017) brazed Cu with Sn-Ag-Cu solder by applying ultrasound and found that the interfacial IMCs became thin and uniform under the effects of USV. Kago et al (2004) reported that the mechanical properties of a Cu/Sn-Bi solder joint were improved by ultrasound application during the solidification stage, which was attributed to the homogenization and thinning of the interfacial layer. Luque de Castro and Priego-Capote (2007) investigated the effect of ultrasound on crystallization; they found that USV could effectively accelerate mass transfer and increase the driving force for crystallization in a mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the cavitation removes the oxide layer on the liquid and solid metals, and promotes wetting and joining at the interfaces. [14][15][16][17][18][19]However, to date, most applications of this technology are joining light metals, especially aluminum. Only a few research on is application to joiningother metallic materials and ceramics has been reported.…”
Section: Introductionmentioning
confidence: 99%